(untitled) (Research, Society and Development, 2022)
The present study aims to identify the mothers of patients with craniofacial anomalies’ perception about the first attendance in a rehabilitation service in the western region of Paraná. This is a qualitative-quantitative and exploratory research, of narrative review, using the Content Analysis method proposed by Bardin and statistical analysis of percentages. Semi-structured interviews were used to collect qualitative data and quantitative data were collected from the applied socionomic study. The population consisted of 20 mothers, of patients aged between 0 and 2 years, inserted in the rehabilitation service. Regarding the mothers’ profile, the data show most are young, with medium and low education, in which a significant portion is exclusively dedicated to housework and child care. As for the characteristics of the family group, a low-income profile stands out, in which 75% of the mothers interviewed have up to 2 children, 65% live on rent and 25% are beneficiaries of a social income transfer program. The mothers’ perception of the first care reveals that there was a change in feelings. Initially, when they arrived at the service, they felt nervous, afraid and shaken. After the multidisciplinary team’s intervention, they reported feelings of tranquility, happiness and safety. The team’s work is perceived as welcoming and trust-promoting. The importance of the work carried out in the promotion of doubts’ clarification regarding the different areas involving the treatment is highlighted. It is evident that the mothers’ first care experience in the specialized service is perceived as positive and points to the formation of a bond with the technical team.